Novel dihydropteroate synthase gene mutation in Pneumocystis jirovecii among HIV-infected patients in India: Putative association with drug resistance and mortality. (June 2019) - Singh, Yogita; Mirdha, Bijay Ranjan; Guleria, Randeep; Kabra, Sushil K.; Mohan, Anant; Chaudhry, Rama; Kumar, Lalit; Dwivedi, Sada Nand; Agarwal, Sanjay K.
Highlights: Dihydropteroate synthase (DHPS) is the target enzyme of trimethoprim/sulfamethoxazole. The DHPS gene of Pneumocystis jirovecii isolates from HIV-infected patients was sequenced. Novel non-synonymous nucleotide substitution observed at position 288 (G → A), resulting in an amino acid change (Val96Ile). Patients infected with mutant P. jirovecii had severe PCP with a fatal outcome. Emergence of a novel P. jirovecii genotype associated with drug resistance is suggested. Abstract: Objectives: Pneumocystis pneumonia (PCP) remains a debilitating cause of death among HIV-infected patients. The combination trimethoprim/sulfamethoxazole (SXT) is the most effective anti- Pneumocystis treatment and prophylaxis. However, long-term use of this combination has raised alarms about the emergence of resistant organisms. This study was performed to investigate mutations in the dihydropteroate synthase ( DHPS ) gene and their clinical consequences in HIV-infected patients with PCP. Methods: A total of 76 clinically suspected cases of PCP among HIV-seropositive adult patients from March 2014 to March 2017 were included. Clinical samples (bronchoalveolar lavage fluid and sputum) were investigated for the detection of Pneumocystis jirovecii using both microscopy and nested PCR. DHPS genotyping and mutational analyses were performed and the data were correlated with clinical characteristics. Results: Among the 76 enrolled HIV-positive patients, only 17 (22.4%) were positive for P. jirovecii . DHPS gene sequencing showed a novel nucleotide substitution at position 288 (Val96Ile) in three patients (3/12; 25.0%). Patients infected with the mutant P. jirovecii genotype had severe episodes of PCP, did not respond to SXT and had a fatal outcome ( P   =  0.005). All three patients had a CD4 + T-cell count <100 cells/μL, and two also had co-infections. Conclusion: This study suggests that the emergence of a mutant P. jirovecii genotype is probably associated with drug resistance and mortality. The data also suggest that DHPS mutational analyses should be performed in HIV-seropositive patients to avoid treatment failure and death due to PCP. However, the role of underlying disease severity and co-morbidities should not be underestimated.